Flow Immersive: A Multiuser, Multidimensional, Multiplatform Interactive Covid-19 Data Visualization Tool - DiBenigno, Michael; Kosa, Mehmet; Johnson-Glenberg, Mina C. (Frontiers in Psychology, 2021)
Covid-19 has prompted a surge of data visualizations published for public consumption, yet many have fallen short of reaching or being understood by the layperson. A data storytelling platform called Flow Immersive has been created to successfully engage both laypeople and experts in understanding complex information. Flow Immersive is a tool that integrates emerging technologies (e.g., augmented (AR) and virtual realities (VR)) with a multiplatform, multiuser publishing approach. From October 2020 to December 2020 Flow’s Covid-19 AR videos captured 9 million views, and have been used in professional presentations. This paper documents several design decisions and the journey to deployment that led to these breakthroughs in engagement and reach.